Multi-resolution simulations of intracellular processes. Issue 3 (19th April 2019) - Erban, Radek; Harris, Sarah; Potestio, Raffaello
Abstract : This is an introduction to the Thematic Issue of Interface Focus containing papers by speakers of the Theo Murphy International Scientific Meeting on 'Multi-resolution simulations of intracellular processes'